2002
DOI: 10.1034/j.1600-0846.2002.80105.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin irritation typing and grading based on laser Doppler perfusion imaging

Abstract: Laser Doppler imaging was found to be an important new method for characterization and grading of the inflammatory response of single exposure irritant reactions. However, standardised study procedures cannot be emphasised enough in order to obtain reliable and useful data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 8 publications
2
24
0
1
Order By: Relevance
“…SLS induced notable localized inflammation with intensity of clinical inflammation and changes in skin perfusion as reported in previous studies [1,21,22]. Topical SLS did not elicit spontaneous pain.…”
Section: Discussionsupporting
confidence: 48%
“…SLS induced notable localized inflammation with intensity of clinical inflammation and changes in skin perfusion as reported in previous studies [1,21,22]. Topical SLS did not elicit spontaneous pain.…”
Section: Discussionsupporting
confidence: 48%
“…This is very relevant in LDPI applications were skin optical properties vary significantly in the region of interest and in time. For example during the uptake of certain drugs or in allergy tests [12] where the skin color changes, the optical properties of the skin vary which influences the signal response irrespective of the perfusion variation. Also in the case of a burn depth [5] or wound healing [6] assessment the changes in absorption and scattering by skin color or a grafted skin influences the measured perfusion signal, not only through the photon statistics, but also because of the speckle effects demonstrated here.…”
Section: Resultsmentioning
confidence: 99%
“…It was demonstrated that skin blood flow, assessed by LDV, may have to be raised 3-4 times before the naked eye can detect changes [107] . Furthermore, using LDI Fullerton et al [108] evidenced that the area with increased perfusion exceeded the area with a clinically visible irritant reaction.…”
Section: Microcirculationmentioning
confidence: 99%